Jember Creative Industry Distribution Model Towards the International Market - Alif Mirzania; Abdul Muhsyi; Agus Priyono (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2022)
The creative industry is one of the industries that currently supports the Indonesian economy. The purpose of this study is to formulate the distribution model of Jember's creative industry towards the international market, especially in the performance art sector. This study is quantitative-eksploratif research conducted in Jember using SMEs as a population. The analytical tool used in this study was FGD and a fishbone diagram. The results of the fishbone diagram analysis showed several causes of SME growth problems such as the lack of HR skills in foreign languages, the inadequate sophisticated technology in business, and the minimal amount of business capital. The inappropriate adoption of the technology was then identified as the root cause of the problem. Thus, the distribution model for the creative industry to increase competitiveness in the international market is the technology application in every element of the SMEs.